Water and environment : proceedings of the 11th Asia-Pacific and 2nd Commonwealth congress of environmental journalists, BARD, Comilla, Bangladesh, September 13-17, 1999 - Chowdhury, Quamrul Islam (Forum of Environmental Journalists of Bangladesh, 2000)
Papers presented at the 11th Annual Congress of Asia-Pacific Forum of Environmental Journalists and 2nd Congress of Commonwealth Environmental Journalists Association.